Developing computer simulations for risk assessment by cable logging rigging crews. Issue 3 (2nd September 2022) - Lyons, C. Kevin; Wimer, Jeffrey; Sessions, John
ABSTRACT: This paper developed six cable logging incident scenarios that were modeled in a simulated environment, and conducted a pilot study in the Pacific Northwest to assess the potential for collecting worker risk assessment data. All the subjects in the pilot study reported that they understood the simulated incidents, and they were able to move around in the simulation to see what they needed. When reporting management requiring conditions (MRC) before performing the simulated task, the subjects consistently identified the first main MRC; however, there was variation in reporting the second main MRC. The results from the pilot study indicate that the simulations effectively modeled the spatial aspects of the incidents; however, the simulations lacked avatars to represent people in the simulations and this may have limited the ability to include cognitive aspects such as communication. Variation in the severity assigned by the subjects to the MRC, and to the unexpected events, revealed important differences in risk sensitivity between the subjects, and the importance of experiential learning in a safe environment when considering energized systems.